The unified dictionary of plastic arts terms : English - French - Arabic (Tunis : Jamiat al-Duwal al-Arabiyah, al-Munazzamah al-Arabiyah lil-Tarbiyah wa-al-Thaqafah wa-al-Ulum, Maktab Tansiq al-Tarib, 1999)
Unified dictionary of plastic arts terms; English-French-Arabic
Arabic, English, and French
1
Keywords: Art -- Dictionaries -- Arabic; English language -- Dictionaries -- Arabic; English language -- Dictionaries -- French